Examination of Turkish and Foreign Female High School Students' Attitudes to Physical Education and Sports Lesson (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to examine the attitudes of Turkish and foreign students towards Physical Education lessons. The data of the research was formed from 304 Turkish and 258 Syrian female students attending Hacı Mehmet Kalay Anatolian Girls’ Imam Hatip High School in Kahramanmaraş by random sampling method in the 2021-2022 academic year. As a data collection tool in the study, “Physical Education Attitude Scale for Secondary Education Students” developed by Güçlü and Güllü (2009) was used. When the attitudes of Turkish and Syrian students towards physical education lesson were compared, no difference was found between the two groups (p=0.649). When the attitudes of the participants to the physical education lessons were examined according to the class variable, it was determined that the 9th grade students had higher scores than the 12th grade students (p=0.021).